The effectiveness of the ELT component at the B.Ed. programme in Bangladesh: A critical perspective - Sultana, Nasreen (Stamford Journal of English, 2013)
The study determines the level of effectiveness of the English course at the B.Ed. programme in Bangladesh in developing professionalism of the prospective English language teachers. Recently, English language teaching has gained momentum because of its local as well as global instrumental use. But, Bangladesh is still facing an acute shortage of skilled English language teachers. Hence, the study investigates the existing structure and the scope of English Language Teaching (ELT) in the teacher training programme of Bangladesh. For this purpose, data has been collected both from trained English language teachers and pre-service trainees to find out the level of success of the ELT course at the B.Ed. programme in Bangladesh. Hence, the study investigates the scope of English language teaching and teacher training with reference to the training institutions in Dhaka, Mymensingh and Comilla. Stamford Journal of English; Volume 6; Page 261-284 DOI: http://dx.doi.org/10.3329/sje.v6i0.13918